Mechanism of visible-light photoisomerization of a rhenium(I) carbonyl-diimine complex - Gindensperger, Etienne; Köppel, Horst; Daniel, Chantal (Chemical communications (Cambridge, England), 2010)
The mechanism of photoisomerization of a Re(I) carbonyl-diimine complex under visible-light irradiation is deciphered by means of ab initio calculations. By highlighting the key role of triplet states as well as spin-orbit and vibronic couplings, we provide a clear picture of this complicated multi-step process.